SOME OBSERVATIONS ON AGRICULTURE AND HORTICULTURE IN THE BUKHARA EMIRATE IN THE EARLY 20TH CENTURY - Kh.P. Juraev (Western European Studies, 2025)
This article examines the development of agriculture and horticulture, the main branches of the rural economy in the Emirate of Bukhara during the early 20th century. It also provides important insights into the primary crop varieties and the distinctive types of horticulture practiced in the region
Keywords: grain; rice; corn; vegetable crops